Pengobatan Menggunakan Ayat-Ayat Al-Quran: Studi Living di Sei Dadap-Kisaran - Aulia, Fatika Anisa; Jamil, Muhammad (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2025)
This study examines the practice of medicine using Qur'anic verses that occurred in Sei Dadap-Kisaran, North Sumatra, within the framework of the Living Qur'an. This practice is part of the religious heritage that is still preserved and developed in the community, and is carried out by local figures such as Mr. Shobari and Mr. Ponidi. This research employs a qualitative approach. The results of the study show that people not only understand the Qur'an textually, but also operationalize it in their daily lives, especially when facing diseases and non-physical disorders. The community widely accepts this practice because it is considered effective in providing inner peace, strengthening spirituality, and fostering a sense of dependence on Allah SWT. From the perspective of sharia and faith, this method falls under the category of ruqyah syar'iyyah, which is justified as long as it does not contain elements of shirk or deviant practices. The study also confirms that Qur'anic medicine is not intended to replace medical treatment, but rather serves as a complementary therapy that strengthens the religious and social dimensions of society. These findings demonstrate how the concept of the Living Qur'an is actualized in the form of contextual, spiritual, and socially impactful treatment practices.